REHABILITATION OF SOILS POLLUTED BY MERCURY (HG) DUE TO GOLD MINING USING LEACHING AND ORGANIC MATTER IN GREEN HOUSE - HARYONO, .; SOEMONO, S (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
The industrial waste, especially that without waste water management instalations caused soil resources degradation. The waste type that has potential to degrade the soil is toxic material, including the heavy metals. Mercury (Hg) is one of the toxic and dangerous heavy metal, which threaten crop, animal, and human health. All types of mercury compound are toxic for human. The mercury is one of the most toxic metal ion to soil biota. Generally, mercury availablility in soil for crop is low, and it tends to accunulate in rootzone. This indicated that the rootzone is a barrier to mercury uptake. The organic material can be used to adsorp the heavy metals. The material have functional array that is active to adsorp the heavy metal if it is ionized. The research was conducted in Soil Research Institute green house using factorial randomized block 3 x 4, with three replications. The first factor is Leaching (without leaching, leached with 1-2 litre pot-1 each three days). The second factor is organic matter (control;cow manure 1,181.47 g pot-1; chicken manure 741.62 g pot-1; straw compost 1,102.29 g pot-1). The research showed that the heavy metal polutions did not affect the rice (IR-64) growth and yield. Organic matter and leaching affect the mercury contents in produced rice. The Hg content from analysis of percolated water is not significantly different. The most effective treatment to lower the mercury content in rice to the level of ?Dirjen POM? (0.05 ppm or 50 ppb) is leaching with 1-2 litre water thatreached 14 ppb and 23 ppb; without leaching reached 25 ppb. Chicken manure with 1 litre water gained 34 ppb and 37 ppb. Organic matter addition with combination of leaching can decrease the Hg content to less the level.